In fond memory of Yakov Borisovich Fainberg (Вопросы атомной науки и техники, 2005)
On March 7th, 2005, Yakov Borisovich Fainberg, the Academician of the National
Academy of Science of Ukraine, passed away. The name of this notable scientist is inseparably
linked with the developments in physics and technique of accelerators, nonrelativistic and
relativistic plasma electronics, plasma physics and controlled fusion.